PREPAREDNESS LEVEL OF STUDENTS IN PRONE SCHOOLS LANDSLIDE DISASTER - Erwin Prastyo; Sigit Saptono; Bambang Subali (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2021)
Abstract: Natural disasters that occur require good disaster preparedness and mitigation efforts. Low knowledge of disasters is one of the factors causing the low attitude toward disaster preparedness. This study aims to analyze the disaster preparedness level of students in landslide-prone schools. The research design used a pre-experimental design, namely one-shot case study. The data were collected using a questionnaire with a purposive sampling technique based on the location of schools in areas that have a high risk of landslides. The data analysis technique uses statistical processing that is descriptive (statistical descriptive). The results showed that the level of students' preparedness attitude in schools prone to landslides was at a low level with an average percentage of 44.17% in five aspects of preparedness. The low level of preparedness is due to the lack of socialization by the school and the lack of inclusion of disaster material in the subject. The results of this study are also expected to provide important information for students and the community to have a natural disaster preparedness attitude and reduce the negative impacts caused by landslides.Abstrak: Bencana alam yang terjadi membutuhkan upaya kesiapsiagaan dan mitigasi bencana yang baik. Rendahnya pengetahuan kebencanaan menjadi salah satu faktor penyebab rendahnya sikap kesiapsiagaan bencana. Penelitian ini bertujuan untuk menganalisis level kesiapsiagaan bencana siswa di sekolah rawan tanah longsor. Desain penelitian yang digunakan pre-experimental design yaitu one shot case study. Pengumpulan data menggunakan kuesioner dengan teknik purposive sampling berdasarkan lokasi sekolah di wilayah yang memiliki risiko tanah longsor yang tinggi. Teknik analisis data menggunakan pengolahan statistik yang bersifat deskriptif (statistic descriptive). Hasil penelitian menunjukkan level sikap kesiapsiagaan siswa di sekolah rawan bencana tanah longsor berada pada level rendah dengan persentase rata-rata 44.17% pada lima aspek kesiapsiagaan. Rendahnya level kesiapsiagaan ini disebabkan oleh kurangnya sosialisasi yang dilakukan pihak sekolah dan minimnya penyisipan materi kebencanaan dalam mata pelajaran. Hasil penelitian ini juga diharapkan dapat menjadi informasi penting bagi siswa dan masyarakat agar memiliki sikap kesiapsiagaan bencana alam dan mengurangi dampak negatif yang diakibatkan oleh bencana tanah longsor.